Semiotics of Signs and Meaning: Analysis of the Poem Derai-Derai Cemara by Chairil Anwar and the Lesson Plan - Eka Putri; Sari, Luciana Lidya; Wahyuni, Sri; Meirani, Wasitoh (Raja Zulkarnain Education Foundation, 2025)
Semiotics is a scientific study that studies the signs contained in a literary work. In essence, semiotics is an effort to reveal all the signs contained in a literary work. Semiotics play a crucial role in constructing a literary work of poetry, enabling the poem to provide the reader with an overview and understanding. The purpose of this study is to describe: 1) the meaning of icons, indexes, and symbols of the poem Derai-derai Cemara by Chairil Anwar; 2) heuristic and hermeneutic reading of the poem Derai-derai Cemara by Chairil Anwar; 3) the plan for learning the signs and meanings contained in the poem Derai-derai Cemara by Chairil Anwar using a constructivist approach in class X of high school. This library research employs a descriptive-qualitative method through a semiotic approach, describing the meaning of iconicity, indexes, symbols, heuristic and hermeneutic readings of poetry, and determining the matrix, model, and variants. The implementation plan for learning is also analyzed using library data. Research results: 1) the meaning of icons, indexes, and symbols of the poem Derai-derai Cemara by Chairil Anwar can be used as reading material and messages to be known by readers; 2) heuristic and hermeneutic reading of poetry in the poem Derai-derai Cemara by Chairil Anwar 3) the lesson plan for learning the meaning of icons, indexes, and symbols and heuristic and hermeneutic reading of poetry in the poem Derai-derai Cemara by Chairil Anwar using a constructivist approach through special teaching materials in class X of high school involving seven core activities.